Penguatan Karakter dalam Komunitas Balee of Education (Boe) Kota Langsa - Febriyantika wulandari (Jurnal Anifa: Studi Gender dan Anak, 2020)
Growing a sense of care and responsibility can be established through the development of knowledge, skills and ethics. Educational and social services programs are the main activities taught to children regularly by the Balee of Education community. This study aims to find the character of responsibility and social care of young citizens conducted by Balee of Education community in Langsa City, Aceh, Indonesia. A qualitative approach with case study methods reveals an individual's increased potential to empathize with others in both the educational and social environments to create a balance in life. The research results indicate that the active participation of individuals can build a positive personality and potential. Through programs based on the concept of learning and sharing, the Balee of Education community in Langsa City has developed its function to shape the character of society through non-formal institutions. Because the development of national character will be achieved if there is synergy from all elements of Indonesian society.